Representations of domestic workers in films La Nana and Dolores Claiborne - Šadl, Zdenka (Teorija in praksa, 2019)
This article examines film representations of domestic workers in the films La Nana (2009) and Dolores Claiborne (1995) through the intersecting perspectives of gender, occupation, citizenship and class. Yet it also emphasises the - otherwise cinematically invisible - multi-dimensional identities of domestic workers via their subjugated storytelling positions. Both women-oriented films use power-relations with other women as the main parameter for their identity-making process on the basis of class, familial and personal groundings, which also intersect with feminist narratives of emotional selves, emancipated from the gender order and embedded in the many possible uses of the word "bitch". The authors find that the forming of protagonists' identities and models of behaviour as women does not depend on men, while the scope of power-resistant possibilities establishes them as multi-dimensional subjects far removed from society's one-dimensional views or conservative media/film representations of domestic workers.
Keywords: Discourse; Diskurz; Film; Gospodinjske delavke; gospodinjske pomočnice; Identiteta (psihologija); Identity (Psychology); reprezentacija; Women household employees